The Human Being in the Context of Educational Construction - Osorio , Tulio Eduardo Suárez (Journal of Ecohumanism, 2025)
The article has theoretical reflections derived from the state of the art of the doctoral thesis Group management as a space of appearance. It questions how the human being finds himself in the context of educational constructions. The approaches, on the one hand, show the intention of leading man through an ideal that is predisposed for him; On the other hand, an education that offers him an incitement to emancipate himself from any regulatory framework, in addition to recognizing himself as a man in constant construction who explores new ways of being and appropriating the world, for this I bring to the text the educational contributions of the theory queer. The method addressed is comprehensive interpretation that allows the texts to be approached without judgments or prejudices.